If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -6 + -3 = 1 Reorder the terms: -6 + -3 + -2x = 1 Combine like terms: -6 + -3 = -9 -9 + -2x = 1 Solving -9 + -2x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -2x = 1 + 9 Combine like terms: -9 + 9 = 0 0 + -2x = 1 + 9 -2x = 1 + 9 Combine like terms: 1 + 9 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| 2(6d+3)=18-3(16d-3d) | | -104=-6x-3x+4 | | 10a+5[a-3]=15 | | 3-x+3=5x | | 6-8x=7x-10+11 | | 14-3a+7a=94 | | 4q+4=-2q-8 | | -6(x-1)=14-2x | | 9x-27=9(11-x) | | 6-2x=-12 | | -2x+4(3x+5)=-60 | | 0.3x-0.4=2 | | 7p-5=69+8 | | 5(x+2)=(x+6) | | -8k+k=-14 | | x/4-x/3= | | .5x+5=17 | | 2(x+1)+4=16 | | 5-3(x-7)=26-2x | | 15+2x-3=2x+5 | | 5(4x+9)=9(2x+3) | | 0.5(14x+8)=6x+8 | | -4m-11=-3m-14 | | 6x+9x-21=105-6x | | -2k-5=-k+3 | | m-9m-8m-5= | | 1+x=x-5 | | 2x+6x+8=36 | | -3(m-8)=3 | | P=22p | | 225-6x=30x+21 | | -3m+16=32-7m |